Back to the basics of polar expeditions: personality hardiness, fear, and nutrition in polar environments - Johnsen, Bjørn Helge; Gjeldnes, Rune (Safety in Extreme Environments People, Risk and Security, 2023)
The present paper aims at presenting an overview of findings relating personality hardiness to adaptation to polar environments. Several studies from the Operational Psychology Research group at the University of Bergen have depicted individual characteristics of high hardy subjects involved in stressful activities in polar environments. These high hardy subjects have superior coping skills, are less influenced by environmental stress, show increased motivation during endurance activities, and have a more adaptive biological stress response. It could be assumed that explorers undertaking solo expeditions in polar environments would represent extremely hardy people. Thus, in addition to previously reported studies on hardiness in polar environment, the results from two previously published papers are presented and re-interpreted. The studies provided a rare opportunity to separate the effects of extreme physiological and emotional strain (mainly fear) and present the trajectory of relevant biomarkers of fear, stress, appetite, and nutritional status during a 90-day expedition across Antarctica. The studies expanded on previous knowledge by showing extreme variations in biomarkers during the expedition and suggested that extreme fear has the highest impact on indicators of stress, stress regulation, appetite, and nutritional status. This, together with the recovery effects found on nutrition status after a daily energy uptake of 5–6000 kcal, expands on previous knowledge about adaptation in polar environments.